Legal Protection of Property Rights Third Parties are Good in Law No. 18 Of 2013 Concerning Prevention and Eradication of Forest Destruction - Donny Victorius (Green Publisher Indonesia, 2021)
Third parties who own property in criminal cases often lack legal protection in recovering their property related to illegal logging This research discusses the legal protection for third parties in the recovery of their stolen property in a criminal act. This encourages this research to be conducted to find out whether there is legal protection for third parties for their property confiscated by the state in the criminal act of illegal logging and how the legislative policy on legal protection for property rights of third parties who have good faith in Law No. 18 of 2013 concerning Prevention and Eradication of Forest Destruction in the future. This study uses a normative legal research approach or literature law research, namely research conducted by examining library materials or secondary data alone. The results of the study concluded that the legal protection in Law No. 18 of 2013 concerning the Prevention and Eradication of Forest Destruction against third parties whose property has been confiscated by the state does not yet exist, resulting in a legal vacuum because normatively there is no legal protection for the property rights of third parties in good faith who become a victim of their property that is confiscated by the state in not criminal illegal logging